SPECT bone scintigraphy in the diagnosis and management of mandibular condylar hyperplasia - S. C. Hodder, J. I. S. Rees,* T. B. Oliver, P. E. Facey, A. W. Sugar (Blackwell Synergy, 2000)
Bone scintigraphy has been used in the diagnosis and planning of treatment of mandibular condylar hyperplasia (hemimandibular elongation) for a number of years.1–3 The purpose of using a bone-seeking radiopharmaceutical agent is to highlight areas of increased osteoblastic activity, but assessment and diagnosis may be difficult.